Effciency of an Electrical Machine in Electric Vehicle Application - Shah, S. B.; Silwal, B.; Lehikoinen, A. (Journal of the Institute of Engineering, 2016)
Machines have always made life simpler, directly or indirectly. They have been developed for a very wide range of applications. For the per- formance analysis of any machine, one important parameter to be considered is the machine loss. This consideration has signifcances like determining the effciency of the machine which in turn infuences the operating cost, determining the heating of machine and for accounting the voltage drops or current component associated with the cause of the losses and many more. Losses in electrical machines can be categorized according to the causes or phenomena that produce them. The effciency of an electrical machine directly depends on different kind of losses in the machine. Therefore, in this paper we primarily focus on the losses in the machine. First, all possible losses, their causes and effects in an electrical machine have been explained. A brief account of calculating those losses has also been explained. The standard method of calculating the effciency follows after that. Finally, a fnite element analysis is performed for a test machine and the losses and the effciency of the test machine is stud- ied. Journal of the Institute of Engineering, 2015, 11(1): 20-29